Lie group symmetries' complete classification for a generalized Chazy equation and its equivalence group - Acevedo, Yeisson A. (2021)
In this work, a complete classification of the Lie group symmetries for a generalization of Chazy equation was carried out and the equivalence group for the generalized Chazy equation is calculated and used to present the principal algebra of the equation.